Basic creep of cement paste at early age - the role of cement hydration. (February 2019) - Wyrzykowski, Mateusz; Scrivener, Karen; Lura, Pietro
Abstract: In this work, the uniaxial creep in compression during the first days of hydration is studied experimentally on cement pastes with w/c of 0.50. In order to assess the effect of the evolving microstructure on creep, the so-called equivalent systems are employed. In these systems, part of the otherwise unhydrated cement is replaced with inert filler (quartz powder). With this approach, non-aging systems are obtained that can emulate specific microstructural features of the real hydrating systems. Despite the very similar elastic Young's moduli of the real and their corresponding equivalent systems, the real hydrating systems experienced much higher creep in the first weeks after loading than the equivalent, inert systems. The differences in creep could be explained either by possibly different morphologies of the hydrates in the two types of systems, intrinsic aging or with the active role of the hydration process in increasing creep (dissolution theory of creep).